(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: This paper provides a review of the existing literature on gastronomic tourism experiences, with a focus on underrepresented perspectives, research domains, and methodologies. Methodology: Employing the PRISMA protocol, a systematic literature review was conducted, analyzing 50 relevant studies published between 2017 and 2023. Results: The findings reveal a significant prevalence of consumer-oriented research within the domain of destination marketing, comprising 88% of the analyzed studies. Conversely, exploration of provider perspectives in the domain of facility marketing is limited, accounting for only 10% of the sample. Moreover, a mere 2% of the total research integrates both consumer and provider perspectives, highlighting a gap in the literature. Methodologically, consumer-centric studies exhibit a preference for quantitative (QUAN) methods, with a notable utilization of the PLS-SEM technique. In contrast, provider-focused studies tend to gravitate towards qualitative (QUAL) methods, such as content analysis. Conclusion: This review underscores the importance of balanced exploration using both QUAL and QUAN methods while considering perspectives from both consumers and providers. Such an approach is essential to achieving a holistic understanding of gastronomic tourism experiences and addressing the current research gap in the field, particularly within the realm of destination and facility marketing.